Chemical Kindling as an Experimental Model to Assess the Conventional Drugs in the Treatment of Post-traumatic Epilepsy - Aghdash, Simin N.; Foroughi, Golsa (CNS & Neurological Disorders - Drug Targets, 2023)
Background: Traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality today, which will surpass many infectious diseases in the coming years/decades. Posttraumatic epilepsy (PTE) is one of the most common debilitating consequences of TBI. PTE is a secondary, acquired epilepsy that causes recurrent, spontaneous seizures more than a week after TBI. The extent of head injury in individuals who develop PTE is unknown; however, trauma is thought to account for 20% of symptomatic epilepsy worldwide. Understanding the mechanisms of epilepsy following TBI is crucial for the discovery of new anticonvulsant drugs for the treatment of PTE, as well as for improving the quality of life of patients with PTE. Objective: This review article explains the rationale for the usage of a chemical model to access new treatments for post-traumatic epilepsy. Results: There are multiple methods to control and manage PTE. The essential and available remedy for the management of epilepsy is the use of antiepileptic drugs. Antiepileptic drugs (AEDs) decrease the frequency of seizures without affecting the disease's causality. Antiepileptic drugs are administrated for the prevention and treatment of PTE; however, 30% of epilepsy patients are drug-resistant, and AED side effects are significant in PTE patients. There are different types of animal models, such as the liquid percussion model, intracortical ferric chloride injection, and cortical subincision model, to study PTE and neurophysiological mechanisms underlying the development of epilepsy after head injury. However, these animal models do not easily mimic the pathological events occurring in epilepsy. Therefore, animal models of PTE are an inappropriate tool for screening new and putatively effective AEDs. Chemical kindling is the most common animal model used to study epilepsy. There is a strong similarity between the kindling model and different types of human epilepsy. Conclusion: Today, researchers use experimental animal models to evaluate new anticonvulsant drugs. The chemical kindling models, such as pentylenetetrazol, bicuculline, and picrotoxin-induced seizures, are important experimental models to analyze the impact of putative antiepileptic drugs.
Keywords: Traumatic brain injury